2018
DOI: 10.5152/kd.2018.14
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Evaluation of the Pathogens Isolated From the Endotracheal Aspirate Samples of the Patients Followed in the Intensive Care Units: A One-Year Retrospective Analysis

Abstract: Objective: The aim of this study was evaluation of distribution of microorganisms and their antimicrobial resistance rates isolated from endotracheal aspirate (ETA) samples of patients under mechanical ventilation in intensive care units (ICUs) of our hospital. Methods: ETS culture results of ICU patients were retrospectively evaluated during one-year period between January 2016 and January 2017. Bacteria isolated from cultures of ETA samples were identified by conventional methods and VITEK ® 2 (bioMérieux, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 5 publications
2
8
0
2
Order By: Relevance
“…3,5 In the study conducted by Sağmak Tartar et al carbapenem resistance was found 97.7% for Acinetobacter isolates. 16 Similar to our data, Altay Koçak et al found that carbapenem, fluoroquinolone, ceftazidime and piperacillin/tazobactam resistance rates of A. baumannii isolates were above 90% and resistance rates were higher in ICUs than in wards. 17 They determined that colistin resistance, which is becoming a worldwide problem, was lower than the national average (2%).…”
Section: Discussionsupporting
confidence: 91%
“…3,5 In the study conducted by Sağmak Tartar et al carbapenem resistance was found 97.7% for Acinetobacter isolates. 16 Similar to our data, Altay Koçak et al found that carbapenem, fluoroquinolone, ceftazidime and piperacillin/tazobactam resistance rates of A. baumannii isolates were above 90% and resistance rates were higher in ICUs than in wards. 17 They determined that colistin resistance, which is becoming a worldwide problem, was lower than the national average (2%).…”
Section: Discussionsupporting
confidence: 91%
“…Increased resistance to carbapenems has been found to be higher in ICUs [16]. Tartar et al found 70.9% resistance rate in 127 of P.auroginosa strains [10]. In our study, the resistance rate of P.aeruginosa to meropenem and imipenem were 48,2% and 51,7%, respectively.…”
Section: Discussionsupporting
confidence: 47%
“…The most common causes of nosocomial infections are LR-TIs which has a high morbidity and mortality rates. The major causes of NLRTIs are gram-negative nonfermentative microorganisms such as Acinetobacter and Pseudomonas [10]. In our study, gram-negative bacteria were isolated in 90 (79.6%) samples.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…(17) %33.3; ETA örneklerinde Tartar ve ark. (18) %100; balgam örneklerinde Orak (19) %100, solunum yolu örneklerinde (ETA ve balgam) Koçak ve ark. (20) %28.6 olarak belirlemişlerdir.…”
Section: Discussionunclassified